Evaluation of the equivalence of different intakes of Fruitflow in affecting platelet aggregation and thrombin generation capacity in a randomized, double-blinded pilot study in male subjects - Das, Ranjit K.; Datta, Tanushree; Biswas, Dipankar; Duss, Ruedi; O’Kennedy, Niamh; Duttaroy, Asim K. (BMC nutrition, 2021)
Background The water-soluble tomato extract, Fruitflow® is a dietary antiplatelet which can be used to lower platelet aggregability in primary preventative settings. We carried out a pilot study to investigate the range of intakes linked to efficacy and to make an initial assessment of variability in response to Fruitflow®. Methods Platelet response to adenosine diphosphate (ADP) agonist and thrombin generation capacity were monitored at baseline and 24 h after consuming 0, 30, 75, 150 or 300 mg of Fruitflow® in a randomized, double-blinded crossover study in male subjects 30–65 years of age ( N = 12). Results were evaluated for equivalence to the standard 150 mg dose. Results Results showed that the changes from baseline aggregation and thrombin generation observed after the 75 mg, 150 mg, and 300 mg supplements were equivalent. Aggregation was reduced from baseline by − 12.9 ± 17.7%, − 12.0 ± 13.9% and − 17.7 ± 15.7% respectively, while thrombin generation capacity fell by − 8.6 ± 4.1%, − 9.2 ± 3.1% and − 11.3 ± 2.3% respectively. Effects observed for 0 mg and 30 mg supplements were non-equivalent to 150 mg and not different from baseline (aggregation changed by 3.0 ± 5.0% and − 0.7 ± 10.2% respectively, while thrombin generation changed by 0.8 ± 3.0% and 0.8 ± 3.1% respectively). Conclusions The data suggest that the efficacious range for Fruitflow® lies between 75 mg and 300 mg, depending on the individual. It may be pertinent to personalize the daily intake of Fruitflow® depending on individual platelet response. Trial registration ISRCTN53447583 , 24/02/2021.